PREVALENCE OF AVIAN INFLUENZA VIRUSES IN LIVE BIRD MARKETS OF LAHORE - M. Sarwar; K. Muhammad; M. Rabbani; M. Younus; N. Sarwar; M. A. Ali; A. Ahad (Journal of Animal and Plant Sciences, 2013)
Prevalence of Avian Influenza Viruses (AIV) in live bird markets of Lahore was determined. A total of 1500 cloacal swabs were collected from seven live bird markets of Lahore, Pakistan for surveillance of the viruses. The samples were tested for virus isolation in chicken embryos. Allanto-amniotic fluid (AAF) of each of the embryos was used for Haemagglutination (HA) test. Eighteen (18/1500) samples were positive for HA activity. AIV Antigen Rapid Test Kit differentiated 4 HA virus as AIV and other 14 as Newcastle disease virus. Haemagglutination Inhibition test also proved four HA positive isolates as AIV, while remaining fourteen as NDV, using specific sera. All the AI virus isolates were confirmed by reverse transcriptase polymerase chain reaction (RT-PCR) using a universal nucleoprotein (NP) primer set specific to the virus NP gene and serotype specific primers (H9 and N2) for its sub typing as H9N2.
Keywords: Avian Influenza virus; H N; live bird markets; RT-PCR